Elite youth sport policy and management. A comparative analysis (Routledge Research in Sport Business and Management, 2017)
Elite youth sport competitions have increased significantly in number in recent years, with the Youth Olympic Games representing the high point of this phenomenon. This book examines the global context within which elite youth sport has emerged and continues to grow. It explores elite youth sport policy across fifteen countries, in Europe, the Americas, Africa and Asia, addressing the questions of how youth talent development is organised and why elite youth sport has become so popular.